Shrimp White Spot Viral Infections Are Attenuated by Organic Acids by Regulating the Expression of HO-1 Oxygenase and β-1,3-Glucan-Binding Protein - Ioan Pet; Igori Balta; Nicolae Corcionivoschi; Tiberiu Iancu; Ducu Stef; Lavinia Stef; Iuliana Cretescu (Antioxidants)
The absence of efficient on-farm interventions against white spot syndrome viral (WSSV) infections can cause significant economic losses to shrimp farmers. With this exploratory study we aimed to test, both in vitro and in vivo, the efficacy of an organic acid mixture (Aq) against WSSV infections in shrimp. In vitro, using shrimp gut primary cells (SGP), 2% Aq significantly reduced WSSV infection and the amounts of H2O2 released but had no impact on CAT and SOD expression. In vivo, in a shrimp challenge test, 2% Aq significantly downregulated the expression of proteins involved in WSSV virulence, such as the lipopolysaccharide-β-1,3-glucan-binding protein (LGBP) and the TLR signalling pathway (LvECSIT), and increased the expression of HO-1 oxygenase. Additionally, at 2% Aq, the expression of the digestive-related enzyme carboxypeptidase B was upregulated in the gut, alongside a significant decrease in IL-22 expression, a cytokine usually increased during WSSV infection in shrimp. A low mortality rate (7.33%) was recorded in infected shrimp treated with 2% Aq compared to the 96.66% mortality in the absence of Aq. The peritrophic membrane (PM) was proven essential to ensure Aq efficacy, as the infected and treated PM deficient shrimp (PM−) had a mortality rate of 27.8%, compared to only 9.34% mortality in the infected shrimp at 2% Aq and in the presence of PM (PM+). Aq significantly increased the expression of mucin-1, mucin-2, mucin-5AC, mucin-5B, and mucin-19 in both PM+ and PM− shrimp. Conclusively, organic acid in mixtures can protect farmed shrimp against WSSV infection and increase their survivability through a mediated gut health effect which includes resistance to oxidative stress and improved immunity.